Recidivism among Icelandic Prison Inmates Released in 2009-2011 - Kjartan Örn Yeoman 1990- (2015)
Countries that expect inmates to return to the community after serving their sentence in prison aim to reduce recidivism. The purpose of this study is to evaluate recidivism rates among inmates who are released from security prisons compared to prisoners released from halfway houses. The study consisted of 322 Icelandic male prisoners that were released back to the community in 2009-2011 after serving a sentence in Iceland and their progress followed up for a two year period. The results show that those who finished their sentence at a halfway house had lower recidivism rates than those who served all their sentence in prison. The mean age was lower among those who recidivated and there was a difference in recidivism rates between offence categories. There were no significant differences in recidivism rates with regard to the number of prior incarcerations. These results could therefore have implications for the Icelandic prison system and future research in the field of forensic psychology. Keywords: Recidivism, prison, age, offence categories, halfway house, criminal history Abstract – Icelandic Þær þjóðir sem gera ráð fyrir því að fangar snúi aftur út í samfélagið stefna að því að koma í veg fyrir endurkomur. Markmið þessarar rannsóknar var að kanna endurkomutíðni meðal fanga sem annars vegar kláruðu sína afplánun í fangelsi eða á Vernd. Rannsóknin samanstóð af 322 íslenskum karlkyns föngum sem luku afplánun á árunum 2009-2011 eftir að hafa afplánað dóm á Íslandi. Helstu niðurstöður voru þær að þeir sem luku afplánun á Vernd voru síður líklegir til þess að fá nýjan dóm að tveimur árum liðnum samanborið við þá sem fóru út úr fangelsum og beint út í samfélagið. Þá var meðalaldur lægri á meðal þeirra sem fengu nýjan dóm auk þess sem munur var á endurkomum eftir brotaflokkum. Þá virtist ekki vera marktækur munur á þeim sem brutu af sér aftur og gerðu það ekki með tilliti til fjölda fyrri brota. Þar að auki ættu niðurstöðurnar að veita ákveðna vísbendingu um íslenska fangelsismálakerfið og gagnast við komandi ...